IDENTIFIKASI JENIS EKTOPARASIT PADA AYAM KAMPUNG SUPER DI DESA ILOHELUMA KABUPATEN BONE BOLANGO - Makmur, Ainsyah Maharani; Datau, Fahria; Nugroho, Tri Ananda Erwin (Jambura Journal of Tropical Livestock Science, 2024)
AbstrackThe super native chicken (Gallus Gallus Domesticus) is the result of a cross between a male native chicken and a female laying breed. Not a few farmers make the maintenance of super native chickens as a livelihood as an economic necessity, besides that super native chickens are also a potential source to meet the protein and animal needs of the Indonesian people. One of the challenges in breeding is the infestation of ectoparasites in the livestock. The impact of ectoparasite infestation such as lice, ticks and mites can cause stress to livestock, reduce productivity and increase the risk of disease transmission. In addition, the impact of ectoparasite infestation often leads to a decrease in the health and quality of production in terms of both meat and eggs, which can cause significant financial losses for farmers. Not many people are familiar with the existence of ectoparasites and their types to the impact caused by ectoparasites, therefore this study aims to identify the types of ectoparasites in super native chickens. The method used was Obsevasional using a Completely Randomised Design (RAL). The samples used in this study were 80 super native chickens. Based on the results of the study, 2 species of ectoparasites were successfully found, namely Geniocotes Gigas and Argas Persicus with a total of 61 individuals.Keywords: Free-range chicken, Ectoparasites, IlohelumaÂ ABSTRAKAyam kampung super (Gallus Gallus Domesticus) merupakan hasil persilangan antara ayam kampung jantan dan ayan ras betina jenis petelur. Tidak sedikit peternak menjadikan pemeliharaan ayam kampung super sebagai mata pencaharian sebagai kebutuhan ekonomi, selain itu ayam kampung super juga menjadi sumber yang potensial untuk memenuhi kebutuhan protein dan hewani masyarakat indonesia. Salah satu tantanngan dalam beternak adalah adanya infestasi ektoparasit pada ternaknya. Dampak dari adanya infestasi ektoparasit seperti kutu, caplak dan tungau dapat menyebabkan terjadinya stress terhadap ternak, mengurangi produktivitas dan meningkatkan resiko penularan penyakit. Selain itu, dampak dari infestasi ektoparasit sering kali menyebabkan penurunan kesehatan serta kualitas hasil produksi baik dari segi daging maupun telur sehingga dapat menyebabkan kerugian finansial yang signifikan bagi peternak. Tak banyak orang mengenal dengan adanya ektoparasit dan jenisnya hingga dampak yang ditimbulkan oleh ektoparasit, oleh karena itu penelitian ini bertujuan untuk mengidentifikasi jenis ektoparasit pada ayam kampung super. Metode yang digunakan yaitu Obsevasional dengan menggunakan Rancangan Acak Lengkap (RAL). Sampel yang digunakan dalam penelitian ini 80 ekor ayam kampung super. Berdasarkan hasil penelitian, berhasil ditemukan 2 spesies ektoparasit yaitu Geniocotes Gigas dan Argas Persicus dengan jumlah total 61 individuÂ Kata kunci : Ayam kampung, Ektoparasit, Iloheluma